Labor Market Power and Financial Leverage: Evidence from Online Job Postings - Bai, John (Jianqiu); Massa, Massimo; Wan, Chi; Wang, Yan (Journal of Financial and Quantitative Analysis, 2026)
Abstract Using the near universe of online job postings from 2007 to 2021, we construct a firm-level metric of labor market power. We find that firms with higher labor market power tend to have higher financial leverage. Our findings are not driven by product market competition or correlated labor market characteristics. The evidence is less pronounced among firms hiring in occupations with high labor mobility and skill transferability. To establish causality, we exploit the establishment of Amazon HQ2 in Crystal City as a shock to the labor market power of local firms and show consistent findings with our baseline results.